Adaptogenic property of Asparagus racemosus: Future trends and prospects. Issue 4 (April 2023) - Singh, Neha; Garg, Meenakshi; Prajapati, Priyanka; Singh, Priyanka Kumari; Chopra, Rajni; Kumari, Anita; Mittal, Avneesh
Abstract: Major depressive disorder (MDD) is a multimodal neuropsychiatric and neurodegenerative illness characterized by anhedonia, continued melancholy, dysfunctional circadian rhythm and many other behavioral infirmities. Depression is also associated with somatic ailments such as cardiometabolic diseases. The existing and upcoming hypotheses have succeeded in explaining the pathophysiology of depression. Only a few of the most validated theories, such as hyperactivity of the HPA axis, activated inflammatory-immune response, and monoaminergic and GABAergic deficit hypotheses, have been discussed in this review. So, an effective and safer alternative approach beyond symptomatic relief has been desired. Therefore, botanical products have steadily been probed to strengthen the modern medicinal system as a promising medicament. In this line, Asparagus racemosus Willd. belongs to Asparagaceace family is the well-documented adaptogen cited in the ancient texts namely, Ayurvedic, Greek, and Chinese medicine system. The whole plant possesses pleiotropic therapeutic activity, antioxidant, anti-inflammatory, immunomodulatory, neuroprotective, nootropic, antidepressant, etc., without showing any remarkable side effects. The literature review has also suggested that A. racemosus administration at varied levels alleviates depression by modulating the HPA axis, increasing BDNF levels, and monoaminergic and GABAergic neurotransmission. Alongside, spikes the level of antioxidant enzymes, SOD, GSH peroxidase, GSH, and catalase in distinct brain regions (i.e., hippocampus, prefrontal cortex, amygdala, and hypothalamus) and promote neurogenesis and neuroplasticity. Thus, it could be a new generation antidepressant that provides relief from both behavioral and somatic illness. The review first describes the plant characteristics, then discusses the hypotheses associated with the pathogenesis of depression, and gives an insight into A. racemosus antidepressant properties and the underlying mechanism. Graphical abstract: Image 1 Highlights: Major depressive disorder is a heterogeneous neurological ailment due to varying etiological and clinical manifestations. Underlying molecular mechanisms such as hyperactive HPA axis, upregulation of pro-inflammatory cytokines, and MAO enzymes, decrease in BDNF level, monoamines level, GABAergic neurotransmission, and many others have partly explained the etiopathology of depression. Phytotherapy as an alternative strategy against standard pharmacological treatment exhibit antidepressant activity via acting on multiple molecular mechanisms. Asparagus racemosus as an adaptogen shows antidepressant-like effects by upregulating and downregulating several molecular pathways.